2017
DOI: 10.1111/jvim.14895
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pretreatment Neutrophil Count on Chemotherapy Administration and Toxicity in Dogs with Lymphoma Treated with CHOP Chemotherapy

Abstract: BackgroundPrechemotherapy absolute neutrophil count (ANC) cutoffs are arbitrary and vary across institutions and clinicians. Similarly, subjective guidelines are utilized for the administration of prophylactic antibiotics in neutropenic dogs.ObjectivesTo evaluate the impact of various ANC cutoffs on chemotherapy administration in dogs with lymphoma treated with CHOP chemotherapy and to determine whether an association between prechemotherapy ANC and subsequent toxicity exists. The secondary objective was to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 62 publications
(164 reference statements)
0
9
0
Order By: Relevance
“…The pre‐chemotherapy ANC used as a cut‐off at the authors’ institution to allow planned chemotherapy to proceed was mostly 2 x 10 9 /l. It has been suggested that a value closer to 1.5 x10 9 /l or even lower may be more appropriate and will help to minimize treatment delays and dose reductions. This could lead to improved tumour responses due to increased dose intensity and should be considered in future prospective canine lymphoma trials.…”
Section: Discussionmentioning
confidence: 92%
“…The pre‐chemotherapy ANC used as a cut‐off at the authors’ institution to allow planned chemotherapy to proceed was mostly 2 x 10 9 /l. It has been suggested that a value closer to 1.5 x10 9 /l or even lower may be more appropriate and will help to minimize treatment delays and dose reductions. This could lead to improved tumour responses due to increased dose intensity and should be considered in future prospective canine lymphoma trials.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, excluding treatment delays inherent to the CHOP19 protocol during the weeks following DOX treatments and overall increased DI would be more likely to result in higher likelihood of high‐grade neutropenic episodes and necessary treatment delays, which has been found to correlate with improved patient outcome. Using a neutrophil count of 1500 cells/μL and above to permit chemotherapy administration was described by Fournier et al as a clinically appropriate cut‐off that would permit the most condensed length of each overall treatment in each protocol, and thus, provide the highest potential DI. Furthermore, it is generally believed that anthracyclines are the most efficacious component of CHOP protocols and we felt that the increased DI of DOX in our CHOP12 would offset any diminished efficacy associated with the lower VCR DI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, excluding treatment delays inherent to the CHOP19 protocol during the weeks following DOX treatments and overall increased DI would be more likely to result in higher likelihood of high-grade neutropenic episodes and necessary treatment delays, which has been found to correlate with improved patient outcome. 4,5,7 Using a neutrophil count of 1500 cells/μL and above to permit chemotherapy administration was described by Fournier et al 14 identical between CHOP12 and CHOP19, the durability of response (ie, PFS) was significantly shorter for CHOP12. The PFS, overall survival and incidence of AE for the current CHOP19 was similar to previous reports of DOX-based protocols.…”
Section: Discussionmentioning
confidence: 99%
“…It is a standard practice at our institution to use a neutrophil cut‐off of 2000/μL prior to chemotherapy administration, which resulted in dose delays for four out of five of the patients evaluated 7 days following treatment with vinblastine at 2.5 mg/m 2 IV. However, a recent publication suggests that utilizing a lower neutrophil cut‐off of 1500/μL does not increase the risk of chemotherapy‐induced toxicity and minimizes dose delays during a 19‐week CHOP protocol . Thus, vinblastine at a dose of 2.5 mg/m 2 may be able to be incorporated into weekly chemotherapy protocols because of the predominantly low‐grade nature of the neutropenia that was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The higher response rates reported in these papers despite the presence of relapsed and refractory lymphoma is likely because of the higher dosages of vinblastine that were utilized, although it is important to note that the use of steroids may have positively influenced the response rate in the study by Lenz et al 13 As expected, GI toxicity at all doses was minimal with all toxic- protocol. 20 Thus, vinblastine at a dose of 2.5 mg/m 2 may be able to be incorporated into weekly chemotherapy protocols because of the predominantly low-grade nature of the neutropenia that was observed. In summary, a formal phase II trial is indicated to determine the response rate and toxicity associated with administration of vinblastine at 2.5 mg/m 2 before a definitive conclusion can be drawn regarding the role of vinblastine at 2.5 mg/m 2 for the treatment of dogs with naive multicentric lymphoma.…”
Section: Discussionmentioning
confidence: 99%